PIJAT LAKTASI UNTUK MELANCARKAN ASI PADA IBU POST PARTUM - Rosa Lubis, Melinda; Juni Ekasari, Dian; Fahnawal, T. Marzila (Universitas Batam, 2024)
The care provided by midwives throughout the life cycle, including pregnancy, childbirth, postpartum, and family planning, is known as comprehensive midwifery. Midwives provide this care to their patients to carry out their duties as midwives. Lactation massage targets several areas, including the breasts, back, shoulders, and neck. The basic idea behind lactation massage is to induce a state of relaxation in the mother, which in turn increases breast milk production by the hormone oxytocin. Since most women do not produce enough breast milk after giving birth, lactation massage aims to stimulate breast milk production. This is due to the fact that a woman's energy levels will be very different after giving birth compared to when she was pregnant, when her milk supply was more stable and the breastfeeding mother felt calmer. This research uses case study methodology, which is a type of descriptive research. By utilizing trackers. There will be a decrease in calcium levels in breast milk when a postpartum mother uses lactation massage to stimulate breast milk production for thirty minutes, twice a day. After giving new mothers a 30-minute lactation massage, researchers found that their breast milk production increased. In short: Women who have recently given birth can benefit from lactation massage by increasing the amount of breast milk they produce.